FLUIDIC PERFORMANCE OF A DUAL-ACTION VITRECTOMY PROBE COMPARED WITH A SINGLE-ACTION PROBE. Issue 11 (21st November 2022) - Steel, David H.; Charles, Martin; Zhu, Ying; Tambat, Sonalee; Irannejad, A. Mani; Charles, Steve
Abstract : Supplemental Digital Content is Available in the Text. The dual-action 20, 000 cpm vitrectomy probes demonstrated a stable fluidic performance and greater aspiration flow, reduced nearfield effects, and lower traction, compared with the single-action 10, 000 cpm probes. Dual-action probes required less vacuum to achieve comparable flow rates. Abstract : Purpose: To assess flow rates, nearfield effects, and traction of a dual-cutting 20, 000 cpm vitrectomy probe (HYPERVIT, Alcon) versus a single-cutting 10, 000 cpm probe (Advanced ULTRAVIT, Alcon). Methods: Flow rates were evaluated for 25+ and 27+ gauge probes using balanced salt solution or porcine cadaver vitreous (biased open, 50/50, and biased closed duty cycles). Probes were suspended in an open beaker, and flow rates were calculated using a precision balance. Nearfield effects and flow pulsatility were assessed using a validated simulation model based on experimental microparticle image velocimetry. Traction was assessed by attaching vitreous to a cantilever beam and measuring the deflection of the beam. Results: For HYPERVIT probes, aqueous flow rates were similar across all cutting rates. Vitreous flow rates increased with increasing cutting rates. At maximum cutting rates, aqueous flow was 62%–67% greater (25+) and 63% greater (27+) with HYPERVIT versus Advanced ULTRAVIT ( P < 0.05); vitreous flow was 44%–47% greater (25+) and 26%–32% greater (27+) with HYPERVIT versus Advanced ULTRAVIT ( P < 0.05). Nearfield effects were reduced, and peak traction forces were significantly lower for HYPERVIT versus Advanced ULTRAVIT ( P < 0.05). Conclusion: Significantly greater aspiration flow, reduced nearfield effects, and reduced traction were observed with dual-action versus single-action probes.